AGE-VARYING ASSOCIATION BETWEEN SUBJECTIVE PHYSICAL FUNCTION AND MEMORY IN COMMUNITY-DWELLING OLDER ADULTS. (11th November 2018) - Sprague, B; Gamaldo, A; Ross, L
Abstract: There are positive relationships between objective physical and cognitive function in older adulthood; however, few studies examine subjective physical and cognitive function despite their frequent use in research and practice. Recent work demonstrated that the impact of age on objective physical-cognitive function relationships varies in direction and magnitude in ways traditional regression analysis cannot adequately address. However, the impact of age on subjective physical-cognitive function is unclear. The goal of the current study was to evaluate the association between subjective physical and cognitive function in a sample of 2693 healthy older adults aged 65–90. Using time-varying effects modeling (TVEM) with age as the time metric, we examined the cross-sectional association between the SF-36 physical function subscale (predictor) and Memory Functioning Questionnaire (outcome) after controlling for gender, education, race, and self-reported health. We found that White participants (b = .07, p < .01) and those reporting higher self-reported health (b = .10, p < .01) had better self-reported memory. Additionally, subjective physical function significantly predicted memory consistently across older adulthood (b =. 004, p < .05). The relationship magnitude did not change, indicating that age may not affect subjective physical-cognitive function relationships like it does with objective physical-cognitive function. Implications for research, including appropriate statistical modeling, will be discussed.